2016 IEEE International Symposium on Circuits and Systems (ISCAS) 2016
DOI: 10.1109/iscas.2016.7538975
|View full text |Cite
|
Sign up to set email alerts
|

An implantable wireless multi-channel neural prosthesis for epidural stimulation

Abstract: This paper presents a fully implantable multi-channel neural prosthesis for epidural stimulation. The prosthesis features three telemetry-operated independent stimulators providing in total eighteen stimulation channels. The stimulator circuits were implemented in a 0.6-µm CMOS technology. The prosthesis is protected in a hermetically sealed ceramic enclosure and encapsulated in medical grade silicone rubber. In-vitro measured results with electrodes in saline are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…The other stimulation parameter ranges are 100-600 Hz for the pulse frequency and 100-500 µs for the pulse width. Comparing the proposed IPG with the literature (Table 2), we propose a system equipped with a greater number of channels, 12 more than those reported in [25] and an order of magnitude greater than other works found in the literature [26,27,29]. Furthermore, the stimulus's maximum PA is 1 mA greater than [27], 2 mA greater than [25], 3 mA greater than [29], and nearly 4 mA greater than [26].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The other stimulation parameter ranges are 100-600 Hz for the pulse frequency and 100-500 µs for the pulse width. Comparing the proposed IPG with the literature (Table 2), we propose a system equipped with a greater number of channels, 12 more than those reported in [25] and an order of magnitude greater than other works found in the literature [26,27,29]. Furthermore, the stimulus's maximum PA is 1 mA greater than [27], 2 mA greater than [25], 3 mA greater than [29], and nearly 4 mA greater than [26].…”
Section: Discussionmentioning
confidence: 73%
“…One of the biggest challenges in the field of sensory feedback via PNS concerns the design of the implantable system; in fact, this must have low energy consumption, have reliable and stable long-term operation, and, obviously, respect the biocompatibility characteristics, have small dimensions and must be able to communicate with the outside. The stimulation waveform used in this study was the symmetric biphasic square wave, as used in the literature both for PNS [12,[25][26][27][28][29] and for TENS [30][31][32][33][34][35] since it was shown to be able to elicit a more comfortable sensation among the other stimulation waveforms. The biphasic square wave settable parameters are the pulse amplitude (PA), the pulse width (PW), the pulse frequency (PF), and stimulation duration (i.e., the number of pulses).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the external current booster using THAT380 was external to the stimulator ASICs, and could be eliminated with a new stimulator ASIC design. 3) Communication Latency: In the first version transmitter design (Jiang et al, 2016), an easyRadio ISM module eRA900TRS was used for the communication with the remote host, chosen for its low power consumption, but it was found that the inter packet delay is not optimal. A BLE radio link is chosen for the second version transmitter design.…”
Section: Discussionmentioning
confidence: 99%
“…A reflux condenser was installed on the flask to keep the volume of the deionized water unchanged. The implant was inductively powered by the first version of the wearable transmitter (Jiang et al, 2016) continuously during the entire course of the accelerated lifetime test. Data packets from the implant were frequently checked to monitor the status of the implant electronics and to ensure the wireless power transfer at a level sufficient for operation.…”
Section: Feasibility For Chronic Implantationmentioning
confidence: 99%